Development of A Backorder P Model for Inventory Management Issues at PLN UID Suluttenggo Considering Revenue Losses - Iqramullah, Syabar; Diawati, Lucia; Sukoyo, Sukoyo (ITB Graduate School Conference, 2025)
PT PLN (Persero) Distribution of North Sulawesi, Central Sulawesi and Gorontalo (UID Suluttenggo) is committed to enhancing the reliability of its new customer connection services. Given the expansive and geographically dispersed operational area, a tiered procurement and material distribution system is implemented. The material distribution process begins at the supplier level and continues to the Customer Service Implementation Units (UP3), which serve as regional distribution warehouses, before being forwarded to Customer Service Units (ULP) based on fluctuating demand. This study aims to model the two-echelon distribution problem by incorporating potential revenue losses resulting from delayed fulfillment (backorders). The problem is formulated within the framework of a periodic inventory model (P-method) with backordering, which falls under the category of nonlinear programming (NLP). The proposed model enables the determination of the optimal ordering cycle and appropriate safety stock levels, with the objective of balancing ordering frequency, storage capacity, and customer service levels. A case study conducted at one of the ULPs in Suluttenggo demonstrates that this approach can lead to more efficient inventory ordering decisions.